Sinensetin attenuates oxygen–glucose deprivation/reperfusion‐induced neurotoxicity by MAPK pathway in human cerebral microvascular endothelial cells. Issue 4 (19th October 2021) - Yang, Dong; Yang, Ronggang; Shen, Jiangyi; Huang, Lu; Men, Shuai; Wang, Tiancai
Abstract: Sinensetin is a polymethoxylated flavone with anti‐inflammatory and anti‐oxidative activities. This work aimed to explore the function and mechanism of sinensetin in oxygen and glucose deprivation/reperfusion (OGD/R)‐induced neurotoxicity. The overlapping target genes of cerebral stroke and sinensetin were determined according to GeneCards and ParmMapper tools and were subjected to Gene Ontology (GO) annotations and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses. Human cerebral microvascular endothelial cells (HCMECs) were stimulated with OGD/R. Neurotoxicity was investigated by Cell Counting Kit‐8, lactate dehydrogenase (LDH) release, reactive oxygen species (ROS) level, qRT‐PCR, and TUNEL analysis. The proteins (p38, JNK, and ERK) in mitogen‐activated protein kinase (MAPK) signaling were measured using Western blotting. Total of 50 overlapping target genes of cerebral stroke and sinensetin were predicted. Pathway analysis showed they might be involved in the MAPK pathway. Sinensetin attenuated OGD/R‐induced neurotoxicity by mitigating viability reduction, LDH release, ROS generation, inflammatory response, and apoptosis in HCMECs. Sinensetin weakened OGD/R‐induced activation of the MAPK pathway via decreasing the phosphorylation of p38, JNK, and ERK. The pathway inhibitors mitigated the activation of the MAPK signaling, and sinensetin exacerbated this effect. The inhibitors reversed OGD/R‐induced neurotoxicity in HCMECs, and sinensetin contributed to this role. Overall, sinensetin prevents OGD/R‐induced neurotoxicity through decreasing the activation of MAPK pathway. Abstract : Sinensetin protected human cerebral microvascular endothelial cells against OGD/R‐induced neurotoxicity by inhibiting the activation of the MAPK pathway. This research provides a new insight in the pharmacological function of sinensetin in OGD/R‐induced neurotoxicity and indicates the therapeutic potential of sinensetin in cerebral stroke.